2017
DOI: 10.1158/1078-0432.ccr-15-3135
|View full text |Cite
|
Sign up to set email alerts
|

Idelalisib Impacts Cell Growth through Inhibiting Translation-Regulatory Mechanisms in Mantle Cell Lymphoma

Abstract: Purpose PI3 Kinase is a critical node in the B-cell receptor pathway which is responsible for survival and proliferation of B-cell malignancies. Idelalisib, a PI3Kδ-isoform specific inhibitor, has been approved to treat B-cell malignancies. While biological activity of the drug has been evaluated, molecular mechanisms and signaling pathway disruption leading to the biological effects of idelalisib are not yet well-defined. Prior laboratory reports have identified transcription and translation as the primary ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
3
3
0
Order By: Relevance
“…Among the four isoforms of PI3K, malignant CLL and other B-cells rely on PI3Kδ/γ, the primary effector of BCR network. Our recent study suggested that in B-cell malignancies, PI3Kδ mimicked a signaling pathway which was previously identified in solid tumors with PI3Kα (8). Several investigations have established that the PI3Kα–mediated signaling cascade influences the cellular metabolome, including glycolysis and energy production (9).…”
Section: Introductionsupporting
confidence: 59%
“…Among the four isoforms of PI3K, malignant CLL and other B-cells rely on PI3Kδ/γ, the primary effector of BCR network. Our recent study suggested that in B-cell malignancies, PI3Kδ mimicked a signaling pathway which was previously identified in solid tumors with PI3Kα (8). Several investigations have established that the PI3Kα–mediated signaling cascade influences the cellular metabolome, including glycolysis and energy production (9).…”
Section: Introductionsupporting
confidence: 59%
“…Mechanism of duvelisib actions were associated with mitigation of AKT, BAD, ERK, and S6 activity, downstream of the B-cell receptor signaling cascade. Similar inhibitory events were reported in B-cell malignancies with idelalisib [49]. …”
Section: Introduction To the Compoundsupporting
confidence: 84%
“…We observed transcriptional suppression with IDE and IBR treatments in CLL cells in vitro, which was most marked when RNA synthesis was initially increased by CD40/IL4. Similarly, a recent study in mantle cell lymphoma also showed that IDE can inhibit protein synthesis which correlated with a reduction in cell size and growth [28]. While a detailed analysis of the genes effected by IDE in CLL has not yet been carried out, a recent clinical study has demonstrated that the CLL cells of patients receiving IBR show primarily a decrease in genes involved in receptor/cytokines signaling and those expressed in proliferating cells, although increased expression of a subset of genes was also observed [29].…”
Section: Discussionmentioning
confidence: 95%